EXPLORING THE GAP IN DESTINATION IMAGE AND DESTINATION PERSONALITY PERCEPTION BETWEEN TOURISTS AND STAKEHOLDERS – CASE OF ROMAN HERITAGE SITES IN SERBIA - Kovačić, Sanja; Jovanovic, Tamara; Šagovnović, Ivana (Turizam, 2019)
The main aim of the paper is to determine if there is a difference in image and brand personality perception of the Roman heritage sites in Serbia between tourism stakeholders and tourists who have visited those sites. The initial assumption was that stakeholders in tourism have a more realistic perception of the current destination brand and image and that they are more aware of advantages and disadvantages related to the development of the analyzed Roman sites.To achieve the main aim of the study, the research has been done in two phases. The first phase included the survey done on the sample of 502 tourists who have visited some of the Roman sites in Serbia, while the second phase included an interview with 10 tourist stakeholders. The results show that tourism stakeholders have a more positive perception of both cognitive and affective image, with a special emphasis on affective image where the differences are quite large. In addition, the results indicate that tourists and tourist stakeholders equally perceive the analyzed Roman sites as Exciting. On contrary, tourist stakeholders have a better perception of all other dimensions of the brand personality, with the biggest difference being noticed in the perception of Ruggedness and Competence. Further differences will be discussed in the paper.